(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2025)
In this edition of “Palimpsest”, twenty-nine authors contributed twenty-two papers, eight of which are co-authored, offering valuable articles and contributions. We extend our gratitude to Elena Shalevska, Mehmet Kahraman, Marija Leontik, Marija Sokolova, Hana Pelouškova, Brikena Kadzadej, Admira Nushi, Jasmina Mojsieva-Gusheva, Sofija Ivanova, Ranko Mladenoski, Mauro Dujmović, Sunčana Tuksar, Luisa Emanuele, Zeki Gűrel, Lindita Kazazi, Aterda Lika, Katica Kjulavkova, Tűrkan Olcay, Özge Nur Ünal, Kamran Akhtar Siddiqui, Anastasija Anastasova, Martina Mihaljević, Maja Pivčević, Jonida Bushi, Ema Kristo, Marisa Janku, Kevin Simonov, Nina Daskalovska, Marina Dimitrieva-Gjorgjievska.